2010
DOI: 10.1111/j.1537-2995.2010.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Receiver operating characteristic curve analysis of circulating blood dendritic cell precursors and T cells predicts response to extracorporeal photopheresis in patients with chronic graft‐versus‐host disease

Abstract: BACKGROUND One proposed mechanism of extracorporeal photopheresis (ECP) in reducing chronic graft-versus-host disease (cGVHD) is alteration in numbers of circulating dendritic cells (DCs). This hypothesis was tested by correlating numbers of DC precursors and T cells in the blood before and during ECP therapy with response of cGVHD. STUDY DESIGN AND METHODS Twenty-five patients with cGVHD were treated with ECP. Data were collected with emphasis on blood cellular markers, clinical response to ECP, and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…Conversely, Akpek GVHD prognostic score seems to have no influence. 17,19 Finally, the observation that earlier ECP initiation may lead to better results 20 was not confirmed by subsequent studies, 19,21,22 and there is no clear evidence about the superiority of an ECP schedule among others. A retrospective study on a large cohort of cGVHD patients found ECP response to be associated with nonmyeloablative transplant, use of donor lymphocyte infusions, and lung involvement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, Akpek GVHD prognostic score seems to have no influence. 17,19 Finally, the observation that earlier ECP initiation may lead to better results 20 was not confirmed by subsequent studies, 19,21,22 and there is no clear evidence about the superiority of an ECP schedule among others. A retrospective study on a large cohort of cGVHD patients found ECP response to be associated with nonmyeloablative transplant, use of donor lymphocyte infusions, and lung involvement.…”
Section: Discussionmentioning
confidence: 97%
“…A 2002 study demonstrated that the presence of expanded clonal T‐cell populations in the peripheral blood of patients before treatment is significantly associated to probability of response . Another group reported that ECP responders have an higher absolute number of CD4+ and CD8+ cells, compared to nonresponders, 3 and 6 months after the onset of ECP, while more recently, the probability of response to ECP was found to be related with the baseline number of circulating myeloid and plasmocytoid dendritic cell precursors and CD4+ and CD8+ lymphocytes . Other studies focused on the B‐cell lineage: authors have shown that there is an association between immature B cells (i.e., CD19+, CD21–) in peripheral blood and response to ECP …”
Section: Discussionmentioning
confidence: 99%
“…12 Dendritic cells, monocytes, and ␥-␦ T cells are also promising as markers after HSCT. 13,14 In cGVHD, B cells and their modulators (eg, B cell-activating factor) are important biomarkers. 15 …”
Section: Cellular Biomarkersmentioning
confidence: 99%
“…Akhtari et al. showed that patients suffering from chronic GvHD with a high starting number of DCs, CD4+, and CD8+ T cells circulating in the peripheral blood responded better to ECP treatment compared with non‐responders. Consequently, before initiating ECP, the determination of DCs and T cells can be considered as a predictor factor of clinical response to ECP in patients with chronic GvHD.…”
Section: Predictor Biomarkers Of Response To Ecp Treatmentmentioning
confidence: 99%